Strongyloides stercoralis prevalence in solid-organ and haematopoietic stem cell transplant candidates and recipients: a systematic review and meta-analysis protocol. Issue 8 (1st August 2022) - Barkati, Sapha; Naeem, Faheel; Hales, Lindsay; Quan, Curtis; Libman, Michael
Abstract : Introduction: Strongyloides stercoralis is an intestinal helminth ubiquitous in tropical and subtropical regions worldwide. It persists in the human host for a lifetime as a result of autoinfection and if undetected and untreated, can lead to increased morbidity and high mortality in immunocompromised individuals such as the transplant population. Transplant patients, including solid-organ and haematopoietic stem cell transplants (SOT and HSCT, respectively), are at a high risk of hyperinfection and disseminated strongyloidiasis. Unfortunately screening is often not systematically performed. Prevalence estimates of Strongyloides in this high-risk population is not well studied. Through this systematic review, we aim to summarise the descriptive evidence on Strongyloides prevalence in SOT and HSCT patients, including diagnostic and screening practices alongside the cases of hyperinfection, disseminated strongyloidiasis and the mortality rate in this population. Methods and analyses: Through the use of various online library databases, we will conduct a systematic review including relevant literature on the prevalence of Strongyloides in SOT and HSCT patients as well as studies assessing hyperinfection and disseminated strongyloidiasis in this patient population. The Population, Intervention, Comparison, Outcome and Study Design strategy and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines will be used to determine a final subset of studies for analysis. Quality assessment for case series and case reports will be determined by a modified quality assessment tool developed by the National Heart, Lung, and Blood Institute (NIH), and the CARE guidelines, respectively. We will provide a narrative synthesis of the findings pertaining to the primary and secondary outcomes of interest (prevalence of Strongyloides and mortality rate in transplant population, respectively) alongside the associated 95% CI. Estimates from individual studies will be pooled using a random effects model. Ethics and dissemination: This systematic review does not require formal ethical approval since no primary data will be collected. Findings will be disseminated through a peer-reviewed publication and relevant conferences. PROSPERO registration number: CRD42021269305.